Degradabilidade ruminai da fibra em detergente neutro e do nitrogênio insolúvel em detergente neutro da silagem de milho e do farelo de soja, em bovinos da raça nelore - Rossi Júnior, Paulo; Boin, Celso; Bose, Máx Lázaro Vieira; Wanderley, Ruy da Carvalheira; Silva, Aliomar Gabriel da (My University, 1997)
The nylon bag in situ degradation thecnique was employed to study the ruminai degradability of the neutral detergent fiber and neutral detergent insoluble nitrogen of the corn silage and soybean meal in four rumen fistulated Nellore steers, averaging 36 months of age and 520 kg of liveweight. A randomized completelcs block experimental design was used, where the animals constituted the blocks. It was used diets with two levels of concentrate: 20 and 40%.The forage used in the diets was corn silage, and the concentrate ingredients were: soybean meal, cottonseed meal, corn grain and sorghum grain. The NIDN degradation rate of the corn silage and the soybean meal showed a decrease of 32,1% and of 46,0 % as a function of the higher concentrate level of the diet, but the effective and potential degradability of this fraction were not affected. Concerning to the NDF, the soluble fraction, potentially degradable and undegrable , were not affected by the increase on the diet concentrate level, but for the corn silage, there were 21,8% of reduction on the effective degradability of NDF. The use of lag time promoted higher degradability values for the studied fraction. The obtained values for some evaluated parameters, different from that assumed by CNCPS, showed the necessity of more data about brazilian used feeds, for model adjustments.
Ruminal degradability of the neutral detergent fiber and neutral detergent insoluble nitrogen of the corn silage and soybean meal in nelore cattle
Keywords: Corn silage; Dynamic of nutrients; Models; Rumen; Soybean meal; Animalia; Bos taurus; Glycine max; Micropus; Zea mays